2007
DOI: 10.1590/s0021-75572007000500007
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonina em crianças com sepse e choque séptico

Abstract: Objectives: To study the behavior of procalcitonin and to verify whether it can be used to differentiate children with septic conditions. Methods:Children were enrolled prospectively from among those aged 28 days to 14 years, admitted between January 2004 and December 2005 to the pediatric intensive care unit at Universidade Estadual Paulista UNESP with sepsis or septic shock. The children were classified as belonging to one of two groups: the sepsis group (SG; n = 47) and the septic shock group (SSG; n = 43).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The method shows good sensitivity and specificity in diagnosing bacterial sepsis at PCT levels of ≥2 ng/ml. [1315] Using PCT levels above 2 ng/ml as the cut-off to indicate sepsis syndrome, the present study showed sensitivity of 86% and specificity of 95%. Using a cut-off of above 0.5 ng/ml revealed higher sensitivity but with a reduction in the specificity to 84%.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The method shows good sensitivity and specificity in diagnosing bacterial sepsis at PCT levels of ≥2 ng/ml. [1315] Using PCT levels above 2 ng/ml as the cut-off to indicate sepsis syndrome, the present study showed sensitivity of 86% and specificity of 95%. Using a cut-off of above 0.5 ng/ml revealed higher sensitivity but with a reduction in the specificity to 84%.…”
Section: Discussionmentioning
confidence: 56%
“…[4] Reduction in concentration of PCT has been described in response to antibiotic administration and may be used to detect antibiotic responsiveness. [91518] In the present study, serial serum PCT levels were not estimated for most patients. However, one of the patients (post-renal transplant status) from this cohort for whom 3 serum PCT levels were performed showed a marked decrease in the PCT levels in response to the antibiotics administered.…”
Section: Discussionmentioning
confidence: 77%
“…(31) In another prospective observational study in a pediatric intensive care unit in São Paulo, Brazil, involving 689 patients admitted within 2 years and including 59 children with criteria for sepsis and 65 children with criteria for septic shock, the plasma levels of PCT at admission allowed differentiation between sepsis and septic shock. (33) These results suggest the validity of using PCT in auxiliary diagnosis of septic conditions in children and its potential usefulness as an indicator of disease severity; the latter may be useful for evaluating the appropriateness of patient hospitalization in the pediatric intensive care unit, for example.…”
Section: Introductionmentioning
confidence: 83%